OPTIMALISASI PEMUNGUTAN TARIF SEWA PASAR PUAN MAIMUN KABUPATEN KARIMUN TAHUN 2015-2016 - Indah Nopriyani; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The research present describe the optimalization collect of rent tariff Puan Maimun Market in Karimun Regency. After the reformation so district government has gived a authority to acclerate the development in their territory. One of the effort by district government are tax and retributions. In Karimun Regecy the government have implemented a district regulation number 9 in 2011 about the retributions and Markets are one op potentions source of retributions likes Puan Maimun Markets. In order that since 2015-2016 the collections of rent tariff on Puan Maimun Markets didn’t get a targets from the realizations.The research use the methode are qualitative methodes that analyze problem research by describe the subject and object conditions based on real fact. This research use location in Karimun city and researcher collect data from books, government regulation, jurnal, mass media, website and deep interview with informan likes Head of Market Business Unit, Secretary of Market Business Unit, staff of collect rent tariff in Puan Maimun Markets and seller in Puan Maimun Markets.The research shows that describe the optimalization collect of rent tariff Puan Maimun Market in Karimun Regency are have done since 2015 and until 2016 the realization of collect retributions market are 21,42%. Some factors cause low of coordinations between goverment with the seller, low of staff that have job to collect the rent tariif of Puan Maimun Market, low of attention seller to pay the market retributions and the minims of some facilities in Markets that support the activity in Markets so many seller in Karimun City that not payed the retributions.Keywords: Optimalizations, Collect, Rent Tariff and Market.